Adherence of Candida albicans to denture base acrylics and silicone-based resilient liner materials with different surface finishes - KADİR, TANJU; ÖZKAN, YASEMİN (SPRINGER HEIDELBERG, 2007)
This study evaluated the surface roughness and Candida albicans adherence on denture base acrylic resins and silicone-based resilient liners with different surface finishes. Four commercial denture base acrylic resins ( three heat polymerized and one room temperature polymerized) and five silicone-based liner materials ( two heat polymerized and three room temperature polymerized) ( 10 x 10 x 2 mm) were tested in this study. The materials were processed against glass or plaster or finished with a tungsten carbide bur. Surface roughness measurements were made using a profilometer with an optical scanner probe. All specimens were ultrasonically cleaned in water for 15 s, autoclave sterilized, and contaminated with C. albicans solution for adherence assay evaluation. The materials processed against the glass surface showed significantly lower surface roughness values (0.11 +/- 0.1-1.66 +/- 1.1 mu m) than those of the materials processed against the dental plaster (2.61 +/- 0.2 6.12 +/- 2.8 mu m) or roughening with a bur (1.48 +/- 0.2 - 7.05 +/- 1.2 mu m; p < 0.05, one- or two-way analysis of variance). Also, the materials processed against the glass surface showed lower C. albicans adhesion ( mean ranks 120.36) than those of the materials processed against the dental plaster ( mean ranks 139.77) or roughening with a bur ( mean ranks 143.06), but the differences were not statistically significant (p > 0.05, Kruskal - Wallis and Mann - Whitney). In all types of surface finishes, C. albicans adhesion on denture base acrylics was significantly less ( mean ranks 90.18 90.40) than those of silicone liners (mean ranks 119.38 205.18; p < 0.01, Kruskal-Wallis).
Keywords: Candida albicans; denture resin; resilient liner; stomatitis; surface roughness; SOFT LINING MATERIALS; ADHESION; INVITRO; GROWTH; STOMATITIS; ROUGHNESS; PELLICLES; INVIVO; SALIVA; SERUM